Hygiene and Ecology - Kirsanova, E. V.; Sokolovskaya, I. A.; Fedorchenko, R. A.; Volkova, Yu. V.; Kutsak, A. V.; Sharavara, L. P.; Кірсанова, Олена Валентинівна; Соколовська, Ірина Анатоліївна; Федорченко, Руслана Анатоліївна; Волкова, Юлія Володимирівна; Шаравара, Лариса Павлівна (Zaporozhye state medical university, 2015)
The authors were guided by the modern teaching standards, verification of theoretical and practical skills due to the assessment within the credit unit system. The case studies, tasks and tests are represented for planning practical classes on Hygiene and Ecology.